2014
DOI: 10.1016/j.brat.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains in internet-based cognitive behaviour therapy for severe health anxiety

Abstract: Objective A sudden gain is defined as a large and stable individual improvement occurring between two consecutive treatment sessions. Sudden gains have been shown to predict better long-term improvement in several treatment studies, including cognitive behavioural therapy for depression and anxiety disorders, but have not been studied in the treatment of health anxiety or any form of internet-based cognitive behavioural therapy. The aim of this study was to investigate the role of sudden gains in internet-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
3
22
0
1
Order By: Relevance
“…Regarding the impact of SGs on treatment outcome measures, sudden gainers had significantly lower panic severity at posttreatment than nonsudden gainers, and this effect was maintained at 6‐month follow‐up, which is consistent with previous reports (Aderka et al, ; Bohn et al, ; Hedman et al, ). Thus, sudden and relatively marked improvements in symptoms, even late in therapy, were maintained several months after finishing treatment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Regarding the impact of SGs on treatment outcome measures, sudden gainers had significantly lower panic severity at posttreatment than nonsudden gainers, and this effect was maintained at 6‐month follow‐up, which is consistent with previous reports (Aderka et al, ; Bohn et al, ; Hedman et al, ). Thus, sudden and relatively marked improvements in symptoms, even late in therapy, were maintained several months after finishing treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In all of these studies (except Hofmann et al, 2006), sudden gainers showed significantly lower anxiety severity scores at posttreatment than nonsudden gainers. However, the conclusions on long-term severity changes are less consistent, with some studies (e.g., Aderka et al, 2012;Bohn et al, 2013;Hedman et al, 2014), but not all (e.g., Hofmann et al, 2006), showing that SGs are associated with lower anxiety severity scores at follow-up.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous research, however, has demonstrated that the majority of improvements in depressive symptoms occur early in treatment (i.e., between sessions one and four; Ilardi & Craighead, 1994) and early symptom change (i.e., change between sessions one and five) significantly predicts treatment response (Lewis et al, 2012). Moreover, sudden gains (i.e., large, rapid, and stable improvements in symptomatology during treatment) have been frequently documented among individuals who respond to CBT for depression (Tang & DeRubeis, 1999), health anxiety (Hedman et al, 2014), and OCD (Rinehart et al, 2013) and these gains have also been found to account for more than half of individuals' total improvement in depressive symptoms (Tang & DeRubeis, 1999). Thus, given that expectancy for anxiety change increased during early treatment sessions (i.e., from pre-treatment to session four), it is possible that nonspecific factors, such as expectancy for anxiety change, may play a role in early symptom change and/or sudden gains during treatment.…”
Section: Discussionmentioning
confidence: 94%